Weed suppression ability and yield performance of rainy season rice varieties under different planting spacing (Journal of the Bangladesh Agricultural University, 2024)
An experiment was conducted during July to November 2016 at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh to find out the effect of planting spacing on weed suppression ability and yield performance of some transplanted Aman (rainy season) rice varieties. The experiment was conducted with four newly developed mutant rice varieties viz., Binadhan-7, Binadhan-12, Binadhan-16 and Binadhan-17, and five plant spacing viz. 25cm × 20cm, 25cm × 15cm, 20cm × 20cm, 20cm × 15cm and 15cm × 15cm in a Split-Plot Design (SPD) with three replications. The lowest weed density was found with Binadhan-7 at 15 cm × 15 cm spacing while the lowest weed biomass was found with Binadhan-16 at 15 cm x 15 cm spacing. On the other hand, the highest crop biomass was found with Binadhan-7 at 25 cm x 20 cm spacing. Variety Binadhan-7 and Binadhan-17 gave higher grain yield than the other two varieties. Among the four varieties, Binadhan-7 gave the best performance in relation to grain yield. The highest grain yield of the variety Binadhan-7 was found at 20 cm × 15 cm spacing (5.38 t ha-1) whereas the lowest grain yield was achieved with the Binadhan-12 at 15 cm × 15 cm spacing (2.60 t ha-1). The highest weed suppression was found in Binadhan-17 while the worst performance in respect to the yield ability was noticed in Binadhan-12. The study concludes that Binadhan-7 could be transplanted at 25 cm x 15 cm or 20 cm × 15 cm spacing to obtain substantial weed control and the best grain yield in Aman season.J Bangladesh Agril Univ 18(2): 227–233, 2020https://doi.org/10.5455/JBAU.91993